Whether waqf and endowment can ride the same legal vehicle in Malaysia? - Syed Abdul Kader, Sharifah Zubaidah; Mohamad, Nor Asiah; Ali, Zuraidah (IIUM Press, 2022)
The concepts of waqf and endowment are used for fund-raising by charitable organisations in Malaysia. This chapter explores the concepts of waqf and endowment and their legal framework to ascertain whether both can co-exist in one legal vehicle. To this end, the chapter examines the various legal vehicles available under Malaysian law that can support the two concepts. It then looks into the legal possibility of implementing both waqf and endowment within one legal vehicle and the challenges arising. The problem relates to the role of the State Islamic Religious Council (SIRC) as sole trustee of waqf, in circumstances where the vehicle chosen is outside of the legal framework provided under the state enactment relating to waqf. The method used is legal doctrinal and comparative legal methodology. This study has found that there are several feasible legal vehicles suitable to undertake waqf and endowment endeavours, nonetheless, due to the automatic vesting of all waqf properties situated in a state on the SIRC, such vehicles would still require the authorisation of the respective SIRC before it may operate and manage waqf. Recommendations will include reform of the law relating to incorporated trustees as well as suggestions for recognition of a legal vehicle that is able to incorporate both, waqf and endowments.